2018
DOI: 10.1371/journal.pone.0205524
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of prescribing practices for older adults treated by female versus male physicians: A retrospective cohort study

Abstract: ImportanceSubtle but important differences have been described in the way that male and female physicians care for their patients, with some evidence suggesting women are more likely to adhere to best practice recommendations.ObjectiveTo determine if male and female physicians differ in their prescribing practices as measured by the initiation of lower-than-recommended dose cholinesterase inhibitor (ChEI) drug therapy for dementia management.Design, setting, and participantsAll community-dwelling Ontario resid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…66,67 Humanistic relationships with patients may enable increased patient disclosure of medical information 65,68 and foster stronger relationships among health team members, thereby improving patient care. Furthermore, female physicians, on average, [51][52][53][54] may obtain more frequent informal consultations with colleagues and be more focused on reading clinical research studies or reviewing a patient's chart when making clinical decisions.…”
Section: Jama Health Forum | Original Investigationmentioning
confidence: 99%
“…66,67 Humanistic relationships with patients may enable increased patient disclosure of medical information 65,68 and foster stronger relationships among health team members, thereby improving patient care. Furthermore, female physicians, on average, [51][52][53][54] may obtain more frequent informal consultations with colleagues and be more focused on reading clinical research studies or reviewing a patient's chart when making clinical decisions.…”
Section: Jama Health Forum | Original Investigationmentioning
confidence: 99%
“…[22][23][24] that medical service provision is related to physicians' risk attitudes [30][31][32][33][34][35] and experience. 36,37 Furthermore, the sex of physicians is associated with treatment 36 and prescribing decisions 38 and with patient outcomes. 39,40 Personality traits are also important to explain decisions and behavior in various contexts.…”
mentioning
confidence: 99%
“…56 Previous work has shown that physician sex is associated with ChEI prescribing patterns. 57 Other work has shown that physicians are influenced by family wishes when deciding whether to prescribe ChEIs. 58 Further work is required to understand the nonclinical factors that may influence prescribing of dementia pharmacotherapy and whether these vary by region.…”
Section: Discussionmentioning
confidence: 99%